Recent Advances in Bifunctional Paramagnetic Chelates for MRI. Issue 9 (14th June 2017) - Giovenzana, Giovanni B.; Lattuada, Luciano; Negri, Roberto
Abstract: Magnetic resonance imaging (MRI) is a non‐invasive diagnostic modality routinely employed in modern clinical medicine to collect images of the internal organs of the human body. Contrast agents (CA) are usually administered to patients to improve the sensitivity of this technique and nowadays these agents are gadolinium complexes. Bifunctional chelating agents (BFCAs) are dual molecules containing a multidentate ligand, able to strongly coordinate a metal ion, and a reactive moiety for conjugation purposes. With BFCAs an easy labelling of biomolecules or vectors with paramagnetic ions is possible, allowing the in vivo MRI visualization of diseases at cellular or molecular level. Abstract :